2022
DOI: 10.3389/fpsyt.2021.780236
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Forensic Mental Health Services and Clinical Outcomes: A Longitudinal Study

Abstract: BackgroundThe COVID-19 pandemic has had a substantial impact on forensic mental health service provision and implementation. This study aimed to provide an analysis of the impact of COVID-19 related restrictions on routine outcomes within a large forensic mental health service in London, UK.MethodWe conducted a longitudinal cohort study using data collected routinely prior to the COVID-19 pandemic (April 2018–March 2020) and then stages thereafter (March 2020–March 2021; analyzed as March–May 2020, June–Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Although these numbers suggest that disease control was rather effective, our data show that the enacted measures concomitantly limited treatment efforts. Notably, a similar impact on therapeutic activities and temporary releases was reported in other states ( Heitzman & Gosek, 2021 ; Kennedy et al, 2021 ; Montanari et al, 2021 ; Puzzo et al, 2022 ). To prevent overcrowding of prisons and to facilitate alternatives to detention, updated regulations for the release of prisoners were approved in 21 out of 27 member states of the European Union in June 2020 ( European Parliament, 2020 ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Although these numbers suggest that disease control was rather effective, our data show that the enacted measures concomitantly limited treatment efforts. Notably, a similar impact on therapeutic activities and temporary releases was reported in other states ( Heitzman & Gosek, 2021 ; Kennedy et al, 2021 ; Montanari et al, 2021 ; Puzzo et al, 2022 ). To prevent overcrowding of prisons and to facilitate alternatives to detention, updated regulations for the release of prisoners were approved in 21 out of 27 member states of the European Union in June 2020 ( European Parliament, 2020 ).…”
Section: Discussionsupporting
confidence: 78%
“…These findings contrast previous studies, reporting increased psychological distress due to COVID-19 in vulnerable groups ( Kozloff, Mulsant, Stergiopoulos, & Voineskos, 2020 ; Yao, Chen, & Xu, 2020 ; Zhu et al, 2020 ). Although a recent publication further suggested that violent incidents in forensic mental health institutions increased during the pandemic, the study did not find increased rates of damage to property and also showed a decrease in non-physical assaults to staff ( Puzzo et al, 2022 ). The fact that physical and non-physical assaults were not subdivided in our study may explain the differing results related to aggressive behavior.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…During this time reduction on average use of NGF tubes by 80.14% was also observed suggesting lesser use of coercive methods to feed adolescents with eating disorders. Given that there are no studies exploring the impact of COVID‐19 restrictions on adolescents within inpatient psychiatric setting, these findings are novel, unexpected and in contrast to what was found among adult inpatients (Flammer et al, 2022; Payne‐Gill et al, 2021; Puzzo et al, 2022). The findings also demonstrate the potential to improve and minimize adverse events in inpatient psychiatric units.…”
Section: Discussionmentioning
confidence: 77%
“…Research exploring the impact of pandemic restrictions on incidence of aggression and use of coercive measures, largely involves psychiatric adult inpatients and have shown mixed results—while some studies suggest a rise in incidence of violence and use of coercive methods (Flammer et al, 2022; Payne‐Gill et al, 2021; Puzzo et al, 2022), some have suggested a decline in aggression and violence within a similar time frame (Feeney et al, 2022; Martin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%